Philosophy of Fala Raha Ternate Culture in Election of Moloku Kieraha - Baharuddin Hi. M.A. Hi. Abdullah (IAIN Ternate, 2021)
Fala Raha is the philosophy of the Sultanate of Ternate, the Sultanate of Ternate is one of the sultanates in Moloku Kie Raha. The cultural philosophy of Fala Raha is the basic understanding of the Ternate community which is applied in the government structure of the Ternate sultanate, the structure of four generations, four symbolic lines, four political powers, four initial communities, four government institutions. Decentralization of post- conflict local elections for regional heads, which is one of the pillars of the democratic party in the regions, has a great contribution to the efforts to realize democracy and good governance in the regions. Direct Pemilkada provides positive and elegant examples that need to be developed and developed by all the elements involved in it. The reality on the ground is that this is not something that is easilyrealized, but positive efforts to achieve this goal must be carried out considering the importance of realizing positive political morale in the implementation of local politics. The purpose of writing is the application of the philosophy of Fala Raha (four houses) in the government structure in the process of regional head elections, with a decentralization theory approach. The result of this journal is to present postconflict local elections based on local wisdom.Keywords : Philosophy of Fala Raha, Decentralization, Pemilukada